DOI: 10.29007/lw5b
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Pressure-Drop in Valve Test-Rig Design

Abstract: Valves are widely used in numerous industries like Beverage, Food, Dairy, Cosmetic, Pharmaceutical and Biotech to serve various purposes. Hence, it is strongly needed that each valve must be tested thoroughly for proper functioning. The equipment used for testing of valves is known as test-rig. At present, no standard test-rig is available in the market for testing of valves. This study is a part of an attempt to develop a cost-effective customized test-rig for multiple valve testing. In present study, pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
4
0
1
Order By: Relevance
“…The foliar spray of GA 3 and NAA might be responsible for rapid increase in cell division and cell elongation in the meristemic region. These findings are in agreement with the findings of Nandekar and Sawarkar (1992), Patel et al, (2010a) and Patel et al, (2010b) they reported that increase in leaf length with the foliar spray of GA 3 and NAA. Singh et al, (1995) and Islam et al, (2007) also supported the leaf length and width increased with these treatments.…”
Section: Leaf Width (Cm)supporting
confidence: 93%
See 3 more Smart Citations
“…The foliar spray of GA 3 and NAA might be responsible for rapid increase in cell division and cell elongation in the meristemic region. These findings are in agreement with the findings of Nandekar and Sawarkar (1992), Patel et al, (2010a) and Patel et al, (2010b) they reported that increase in leaf length with the foliar spray of GA 3 and NAA. Singh et al, (1995) and Islam et al, (2007) also supported the leaf length and width increased with these treatments.…”
Section: Leaf Width (Cm)supporting
confidence: 93%
“…Thus, reduction in plant height is due to retardation of transverse cell division particularly in cambium which is the zone of meristamatic activity at the base of the internodes. These results are in close conformity with those of Suheela et al, (2005), Islam et al, (2007, Bose et al, (2009), Rashid (2010), Patel et al, (2010a), Patel et al, (2010b, Ouzounidou et al, (2011), Govind et al, (2015, Shashi Kumar and Shashidhar (2016) and Thakur et al, (2018).…”
Section: Pl Ant H Eightsupporting
confidence: 90%
See 2 more Smart Citations
“…The results can be compared with that of [13] who concluded that spray of thiamethoxam remained best against mango hoppers. Similarly the results are not in line with that of [14] who stated that two sprays of thiamethoxam against mango hoppers on mango crop effectively prevented the hopper population. The other important aspect is the pollinator at flowering stage which plays an important role in fruit setting, their shortage leads to failure of yield.…”
Section: Module-iiicontrasting
confidence: 85%